Dakwah Strategy in The Modern Era - Alwaan, Alfathir Zahy; T, Nur Asia (STKIP Pesisir Selatan, 2024)
This research aims to explore contemporary da'wah approaches. To remain relevant and effective in conveying the message of Islam to the wider community, da'wah strategies must be updated in the face of rapid social and technological dynamics. This research will investigate the various methods and tools used by preachers and da'wah institutions to spread Islamic teachings through a case study approach and a qualitative approach. It is hoped that a da'wah model that is adaptive to current developments can be found by understanding how effective these methods are in reaching diverse audiences. Document analysis to understand the theoretical and historical context of the da'wah strategies used, comprehensive interviews with preachers, ulama, and community members involved in da'wah activities, and participant observation to see directly the practice of da'wah communication. This research is expected to make a significant contribution to research on Islamic communication and da'wah because the data collected from various sources is triangulated. It is hoped that the results of this research will provide a deeper understanding of how Indonesian society accepts Islamic communication methods. These results will also provide information about the challenges and opportunities associated with creating a da'wah strategy that is inclusive and appropriate to the needs of modern society. This research is not only academically relevant but also has practical benefits in helping preachers, da'wah institutions, and policy makers advance Islamic da'wah in the digital era